Robust trading for ambiguity-averse insiders - Vitale, Paolo (Journal of Banking & Finance, 2018)
In an asset market with explicit trading rules we characterize the trading activity of an ambiguity-averse insider who faces Knightian uncertain over other market participants’ beliefs and implements a robust trading strategy. Such insider employs a max-min choice mechanism, so that in any round of trading she selects as her market order that which maximizes her expected profits against those market beliefs which penalize her most. Her trading strategy is equivalent to that of a risk-averse insider who does not face any Knightian uncertain and possesses risk-sensitive recursive preferences. As she finds it optimal to trade more aggressively and reveal her private information at a faster pace than her risk-neutral (expected-profit maximizer) counterpart, we find that ambiguity-aversion is beneficial to the efficiency of the market.